2013
DOI: 10.1128/jvi.03497-12
|View full text |Cite
|
Sign up to set email alerts
|

The Myeloid Transcription Factor GATA-2 Regulates the Viral UL144 Gene during Human Cytomegalovirus Latency in an Isolate-Specific Manner

Abstract: It is generally accepted that, following primary infection, human cytomegalovirus (HCMV) establishes lifelong latency in CD34؉ progenitor cells and other derivative cells of the myeloid lineage. In this study, we show that the viral UL144 gene is expressed during latent infection in two cell types of the myeloid lineage, CD34؉ and CD14 ؉ monocytes, and that the UL144 protein is functional in latently infected monocytes. However, this latency-associated expression of UL144 occurs only in certain isolates of HCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(103 citation statements)
references
References 65 publications
0
103
0
Order By: Relevance
“…25 This may in part be explained by recent evidence suggesting that latent infection itself may result in some partial commitment of CD34 1 progenitors to the myeloid lineage. 28 Consistent with cells of the myeloid lineage being sites of latent infection, analyses of the viral transcription programme in these cells generally shows a suppression of viral lytic gene expression 2,29-32 but concomitant expression of known latency-associated viral genes. 31,[33][34][35][36][37] Importantly, these cells do not produce infectious virions; an essential characteristic of latent infection.…”
Section: Establishment Of Latency and The Molecular Biology Of The Lamentioning
confidence: 85%
“…25 This may in part be explained by recent evidence suggesting that latent infection itself may result in some partial commitment of CD34 1 progenitors to the myeloid lineage. 28 Consistent with cells of the myeloid lineage being sites of latent infection, analyses of the viral transcription programme in these cells generally shows a suppression of viral lytic gene expression 2,29-32 but concomitant expression of known latency-associated viral genes. 31,[33][34][35][36][37] Importantly, these cells do not produce infectious virions; an essential characteristic of latent infection.…”
Section: Establishment Of Latency and The Molecular Biology Of The Lamentioning
confidence: 85%
“…Investigators have previously reported that US28 is expressed during latency in natural (32,45) and experimental (4-6, 44, 49) …”
Section: Generation Of Viral Recombinantsmentioning
confidence: 99%
“…Although many studies have focused on understanding US28's functions during lytic replication (reviewed in reference 48), there is little known about the role US28 plays during latency although it is one of only a few genes associated with latent transcription. US28 transcripts have been detected both during natural latency (32,45) and during ex vivo latent infection studies (4-6, 44, 49). To begin to elucidate the role of US28 during latency, we have utilized the Kasumi-3 model for HCMV latency and reactivation (23).…”
mentioning
confidence: 99%
See 2 more Smart Citations